Detectability evaluation of the loose parts in steam generator by eddy current testing techniques - Kyungcho Kim; Kyongmahn Min; Changkuen Kim; Jin-Gyum Kim; Myungjo Jhung (Nuclear Engineering and Technology, 2018)
Detectability of the loose parts (LPs) in steam generator (SG) was studied with eddy current testing technique such as X-probe, bobbin and rotating coils (MRPC®) as a function of LP size and spacing between LP and tube or between LP and support structures. SG mockup simulating SG tube and support structures with LP was fabricated. The X-probe showed slightly better detectability than MRPC® for LP of ferrous (F-LP) material and vice versa for LP of nonferrous (NF-LP) material. In terms of feasibility, inspection rate and other predictable features of the SG tubing inspections, X-probe can be used reliably for monitoring the LPs and the flaws formed by LPs on SG tubes. Keywords: SG, ECT, Loose parts, X-probe, Bobbin, MRPC®